Proposta metodológica de compreensão da problemática das relações entre uso do solo e transportes no planejamento urbano integrado - Soares, Fernanda Duarte Peixoto (2014)
The current lack of integration between land use and transportation systems within the urban planning process, coupled with the lack of a clear method to understand these relationships, has resulted in urban and transportation plans that highlight the need for an unified approach towards urban issues in favor of better conditions of mobility and accessibility. This research attempts to propose a better systematization of the problem understanding phase within the integrated urban planning process of land use and transport, which relates to the current urban mobility planning paradigm, that focuses on the accessibility in order to support the establishment of strategic objectives and subsequent alternative proposals. The specific objectives set for this research seek to identify conceptual and methodological gaps in land use and transportation integrated urban planning, highlighting the relevance of the problem understanding phase within the process, and to propose an identification, characterization and diagnosis method of the relationship between land use and transportation, as well as to discuss the role of integrated modelling and analysis tools in support of the related activities. This work contribute to the scientific and technical realms as the proposed method is capable to assist in the development of planning instruments aimed at the strategic level, as Urban and Mobility or Transportation Plans, giving the process the much need rationality that an applied science activity requires.